Understanding the effects of nanocarbons on flexible polymer chain orientation and crystallization: Polyethylene/carbon nanochip hybrid fibrillar crystal growth. Issue 18 (18th April 2014) - Green, Emily C.; Zhang, Yiying; Minus, Marilyn L.
ABSTRACT: Polyethylene (PE)/carbon nanochip fibers (CNCF) fibrillar crystals were grown under shear flow. The fibrillar crystals ranged from 25 to 200 nm in diameter and bundled to form PE/CNCF macro‐fibers. The PE/CNCF fibers were further processed by hot‐drawing near the PE melting temperature. On the basis of small‐angle X‐ray analysis, it was found that during drawing the presence of CNCF led to continuous extended‐chain PE crystal growth. DSC melting peaks associated with transformation of the orthorhombic to a hexagonal lattice phase in the PE crystal structure (i.e., increased ordering and extension of the polymer chain along the fiber axis) was also observed for drawn hybrid PE/CNCF fibrillar crystals. The orientation factor for the extended‐chain (i.e., shish) crystals in the hybrid as compared to the control fibers improved from 0.88 to 0.93. This work shows the direct evidence that these nanocarbon fillers can promote extended‐chain polymer crystal growth under shear. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2014, 131, 40763. Abstract :